2020
DOI: 10.1038/s41598-020-74390-5
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli foster bladder cancer cell line progression via epithelial mesenchymal transition, stemness and metabolic reprogramming

Abstract: Bacteria is recognized as opportunistic tumor inhabitant, giving rise to an environmental stress that may alter tumor microenvironment, which directs cancer behavior. In vitro infection of the T24 cell line with E. coli was performed to study the bacterial impact on bladder cancer cells. EMT markers were assessed using immunohistochemistry, western blot and RT-PCR. Stemness characteristics were monitored using RT-PCR. Furthermore, the metabolic reprograming was investigated by detection of ROS and metabolic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
(64 reference statements)
2
18
0
Order By: Relevance
“…Upon correlating the OXPHOS signature with the Hallmark EMT scores, we found that although there were significant correlations both in the positive and negative directions, there were many more datasets correlated negatively (56 vs. 24) with Hallmark EMT than were correlated positively (Fig 2A). This overall observation is in accordance with many experimental studies that point towards a negative association between oxidative phosphorylation and EMT [36][37][38][39]. However, this relationship is not exclusive, i.e.…”
Section: Oxphos Is More Likely To Be Negatively Correlated With a Mesenchymal Program And Positively With An Epithelial Onesupporting
confidence: 92%
“…Upon correlating the OXPHOS signature with the Hallmark EMT scores, we found that although there were significant correlations both in the positive and negative directions, there were many more datasets correlated negatively (56 vs. 24) with Hallmark EMT than were correlated positively (Fig 2A). This overall observation is in accordance with many experimental studies that point towards a negative association between oxidative phosphorylation and EMT [36][37][38][39]. However, this relationship is not exclusive, i.e.…”
Section: Oxphos Is More Likely To Be Negatively Correlated With a Mesenchymal Program And Positively With An Epithelial Onesupporting
confidence: 92%
“…Hyaluronic acid (HA) is the main ligand for CD44, which is a constituent of the extracellular matrix (ECM) and it is expressed by stromal and cancer cells. It illustrated that CD44 may serve as microorganisms binding site, so that E. coli could bind to HA adherent to CD44 on urothelial cells, which facilitates E. coli migration through epithelial cells [31]. Interestingly, when a biofilm is detected on a tumor, its flanking normal tissue is mostly also covered by biofilm, suggesting that it expands over long distances in the tumor environment.…”
Section: Resultsmentioning
confidence: 99%
“…While previous research has examined the relationship between intra-tumoral microbes and EMT, almost no study examined such a relationship in MIBC or other forms of bladder cancers. The sole study that has explored this topic, to the best of our knowledge, found that urinary E. coli isolated from a bladder cancer patient was able to promote EMT in bladder cancer cell lines [20]. However, this study only profiled one bacterial species derived from a single patient.…”
Section: Discussionmentioning
confidence: 98%